Evaluation of endothelial function - Antoniades, C; Antonopoulos, A; Tousoulis, D; Shirodaria, C; Bakogiannis, C; Stefanadis, C (Nova Science Publishers, Inc., 2011)
Endothelium is a multifunctional signal-transducing surface that regulates vascular homeostasis through the release of a variety of autocrine and paracrine substances, that can lead to the development of atherosclerotic plaques. Therefore, the invasive and non-invasive assessment of endothelial function is widely used as an experimental tool in clinical research, while strong evidence suggests that it could also be used in clinical practice in the near future. Several invasive and non-invasive techniques have been developed during the last two decades to evaluate and quantify endothelial dysfunction. Invasive techniques which involve intracoronary or intrabrachial infusions of vasoacting agents are still considered to be the gold standard for the early detection of endothelial dysfunction. Non-invasive techniques include flow-mediated dilatation (FMD) of peripheral arteries using an ultrasound probe, gauge-strain plethysmography that uses the changes in impedance to evaluate the changes in forearm blood flow during reactive hyperemia and magnetic resonance imaging (MRI) which bears great potential in evaluating vascular anatomy and function due to its high temporal and spatial resolution compared to ultrasound-based techniques. All of these techniques contribute the identification of endothelial dysfunction that mandates more aggressive treatment and better control of cardiovascular risk factors in order to improve patients' prognosis. © 2011 Nova Science Publishers, Inc. All rights reserved.